Rapid increase in atmospheric iodine levels in the North Atlantic since the mid-20th century - Cuevas, Carlos A. (2018)
Atmospheric iodine causes tropospheric ozone depletion and aerosol formation, both of which have significant climate impacts, and is an essential dietary element for humans. However, the evolution of atmospheric iodine levels at decadal and centennial scales is unknown. Here, we report iodine concentrations in the RECAP ice-core (coastal East Greenland) to investigate how atmospheric iodine levels in the North Atlantic have evolved over the past 260 years (1750–2011), this being the longest record of atmospheric iodine in the Northern Hemisphere. The levels of iodine tripled from 1950 to 2010. Our results suggest that this increase is driven by anthropogenic ozone pollution and enhanced sub-ice phytoplankton production associated with the recent thinning of Arctic sea ice. Increasing atmospheric iodine has accelerated ozone loss and has considerably enhanced iodine transport and deposition to the Northern Hemisphere continents. Future climate and anthropogenic forcing may continue to amplify oceanic iodine emissions with potentially significant health and environmental impacts at global scale.